Upcycling mine tailings into functional materials for environmental remediation and energy storage applications - Peter, Rexy Niro Anak; Zheng, Alvin Lim Teik; Koo, Lee Feng; Wong, Tze Jin; Andou, Yoshito (Springer, 2025)
Mine tailings (MT), a byproduct of mining operations, often pose significant environmental and economic challenges. Traditional disposal methods often lead to contamination of water bodies, soil, and air, negatively impacting ecosystems and human health. To address these issues, this review explores the potential of transforming MT into valuable functional materials through a waste-to-value approach. By employing various modification strategies, the physicochemical properties of MT can be significantly improved, unlocking their potential for diverse applications. This review investigates the conversion of tailings into functional materials for wastewater treatment and energy applications. Additionally, the study highlights recent advancements in the recovery of functional materials from MT, identifying key challenges and opportunities for future research and development. This review contributes to a more circular economy and sustainable mining practices by exploring the potential of MT-derived functional materials.